Early life stress and chronic variable stress in adulthood interact to influence methamphetamine self-administration in male rats. Issue 2 (April 2016) - Lewis, Candace R.; Staudinger, Kelsey; Tomek, Seven E.; Hernandez, Raymundo; Manning, Tawny; Olive, M. Foster
Abstract : Early life stress interacts with adult stress to differentially modulate neural systems and vulnerability to various psychiatric illnesses. However, the effects of early life stress and adult stress on addictive behaviors have not been sufficiently investigated. We examined the effects of early life stress in the form of prolonged maternal separation, followed in early adulthood by either 10 days of chronic variable stress or no stress, on methamphetamine self-administration, extinction, and cue-induced reinstatement. We observed that chronic variable stress in adulthood reduced methamphetamine self-administration in rats with a history of early life stress. These findings add to an emerging body of literature suggesting interactions between early life and early adulthood stressors on adult behavioral phenotypes.